أزمة الحداثة العربية على تخوم المشروع الحضاري البديل - عزوز بن عمر الشوالي (International Institute of Islamic Thought, 2019)
مشروع الاستئناف الحضاري للأُمَّة العربية الإسلامية اليوم هو برنامج تنموي استشرافي، يهدف إلى تقديم رؤية جديدة تستفيد من الرصيد الفكري التليد الذي أنجزته حركة الإصلاح العربية الإسلامية الحديثة على يد أنجب علماء الأُمَّة وخيرة مفكِّريها من أعلام النهضة، أمثال: جمال الدين الأفغاني، ومحمد عبده، وعبد الرحمن الكواكبي، وخير الدين التونسي، وعبد الحميد بن باديس، ومحمد الطاهر بن عاشور، وشكيب أرسلان، ومالك بن نبي، وغيرهم. لكن هذا المشروع لا يُكرِّر التجربة التاريخية لمشروع الإصلاح والنهضة السابق، وإنَّما يعيد قراءته وتوظيفه تبعاً لمستجدات الظروف والسياقات، وبحسب مبدأ اجتناب الإخفاقات التي أغرقت مشروع النهضة، وانتهت به إلى الفشل والجمود. إنَّ هذا المشروع البديل هو رؤية تنموية، ونتيجة منطقية نجمت عن مسار محفوف بالأزمات والإخفاقات التي حالت دون تحقيق النهضة والتحوُّل الحضاري بأدواته الحقيقية ونتائجه الصحيحة. The contemporary project of the civilizational resumption of the Arab-Muslim nation today is a prospective developmental program aims at presenting a new vision that takes advantage of the intellectual legacy achieved by the modern Arab-Muslim reform movement at the hands of the scholars and thinkers of the Renaissance, such as: al-Afghani, Abdo, al-Kawakibi, al-Tunisiani, Ben Badis, Ben Achour, Chakib Arslan, Malik bin Nabi, and others. However, this project does not repeat the historical experience of the previous reform and renaissance one, rather it rereads and employs its experience according to the latest circumstances, trying to avoid the failures that plunged the Renaissance project and caused its failure and stalemate. This alternative project is a developmental vision and logical consequence of a path fraught with crises and failures that prevented the realization of the renaissance and the civilizational transformation with its correct tools and results.